Maize-soybean intercropping for sustainable intensification of cereal-legume cropping systems in northern Nigeria - Kamara, A.Y.; Tofa, A.I.; Ademulegun, T.; Solomon, R.; Shehu, H.; Kamai, N.; Omoigui, L.O. (Cambridge University Press, 2019)
Field studies were conducted during the 2014 and 2015 wet seasons at Zaria in the northern Guinea savanna and at Iburu in the southern Guinea savanna of Nigeria to determine the productivity of maize– soybean intercropping system. There were four treatment combinations in the experiment: sole maize; sole soybean; maize spaced at 50 cm and intercropped with soybean; and maize spaced at 65 cm and intercropped with soybean. The experiment was laid out in a randomized complete block design with three replications. The results showed that sole cropped maize and soybean generally outperformed the intercropped component crops. Land Equivalent Ratio (LER) was greater than 1 for all the intercrop treatments, indicating that it is advantageous to grow maize and soybean in association than in pure stands. Except for 2014 in Zaria, LER for intercropped maize spaced at 50 cm was higher than that for maize spaced at 65 cm. Gross Monetary Value (GMV) was generally higher for intercrops than sole crops except in Iburu in 2015 where GMV for intercropped maize spaced at 65 cm was similar to those of sole maize and soybean. Monetary Advantage Index (MAI) was positive for all intercrop treatments in both locations and years, which shows definite yield and economic advantages compared to the sole cropping systems. This suggests that farmers can intercrop soybean and maize with maize spaced at 50 cm and 65 cm.